2005
DOI: 10.1159/000086434
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of c-<i>myb</i> in Leukaemic and Non-Leukaemic Variants of Cutaneous T-Cell Lymphoma

Abstract: Background: The c-myb oncogene is a transcription factor that regulates proliferation, differentiation and apoptosis of haematopoietic cells and activated T cells by binding to promoter sequences of such genes as c-myc or bcl-2 that are expressed in cutaneous T-cell lymphoma (CTCL). Objective: Our study was performed in order to evaluate c-myb expression as a quantitative parameter for differential diagnosis in leukaemic and non-leukaemic variants of CTCL. Methods: c-myb expression was analysed in lesional ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…18 Interestingly, we have previously reported that c-myb is consistently overexpressed in PBMC from SS patients, but not PBMC from MF patients. 19 Upregulated c-myb may well contribute to upregulation of CDO1 in SS PBMC indicating hierarchical pathways in the molecular pathogenesis of SS.…”
Section: Discussionmentioning
confidence: 99%
“…18 Interestingly, we have previously reported that c-myb is consistently overexpressed in PBMC from SS patients, but not PBMC from MF patients. 19 Upregulated c-myb may well contribute to upregulation of CDO1 in SS PBMC indicating hierarchical pathways in the molecular pathogenesis of SS.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the overlapping clinical features of T-prolymphocytic leukemia (previously known as T-CLL) and SS [56, 57], it is conceivable that if TCL1 expression persisted later in T-cell differentiation pathway than normal, perhaps through an epigenetic or posttranslational mechanism [58], then SS might develop. Alternatively, a genetic defect such as c-myb activation may contribute to the emergence of SS from TCL1 expressing precursor cells [59]. …”
Section: Discussionmentioning
confidence: 99%
“…Myb genes (a-myb, b-myb and c-myb) are a family of transcription factors whose expressions have been implicated in the control of the proliferation and differentiation of normal and transformed cells [7]. Among these, c-myb proto-oncogene is the best characterized member of the myb family of transcription factor genes.…”
Section: Introductionmentioning
confidence: 99%